1973
DOI: 10.1172/jci107405
|View full text |Cite
|
Sign up to set email alerts
|

The Subunit Structure of Normal and Hemophilic Factor VIII

Abstract: A B S T R A C T Human factor VIII froml nornmals anid hemophiliacs was partially purified by ethaniol and polyethylene glycol precipitations. Final purification was achieved by gel filtration on 2 or 4%Xc agarose or ion1 exchange chromatography on diethylaminoethyl cellulose. Comparable amounts of highly purified protein were obtained from normal and hemophilic plasma following the agarose chromatographv step. Highly purified factor VIII was not dissociated by 6 -MI guanidine hydrochloride or 1% sodium dodecyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

1975
1975
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(42 citation statements)
references
References 28 publications
2
39
1
Order By: Relevance
“…The protein and procoagulant elution patterns of normal cryoprecipitate have been previously described (2)(3)(4)(5)(6). A low level of protein associated with the bulk of the procoagulant activity begins to elute at the void volume (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The protein and procoagulant elution patterns of normal cryoprecipitate have been previously described (2)(3)(4)(5)(6). A low level of protein associated with the bulk of the procoagulant activity begins to elute at the void volume (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…The human Factor VIII/von Willebrand Received for publication 28 January 1975 and in revised form 11 June 1975. 'Abbreviations used in this paper: F. VIII/vWF, Faccharacterized as a high molecular weight glycoprotein with a major subunit of 195,000-240,000 mol wt (1)(2)(3)(4)(5)(6). In severe von Willebrand's disease (vWD), the deficiency of procoagulant and vWF activity (as judged by the ristocetin assay) is associated with a marked deficiency or absence of the F.VIII/vWF protein (7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…SDSgel electrophoresis of reduced samples of purified vWf yields a single subunit of -240,000 mol wt (8,15,16). Recent characterization of the cyanogen bromide fragments of carboxymethylated vWf (17) provides additional strong evidence that the circulating forms ofvWfare polymers composed ofa single type ofsubunit.…”
Section: Introductionmentioning
confidence: 99%
“…Human antihemophilic factor (Factor VIII) eluted near the void volume when plasma or Factor VIII concentrates were chromatographed on 2-4% agarose in dilute, neutral buffers (1)(2)(3)(4)(5)(6)(7). The s25 .…”
Section: Introductionmentioning
confidence: 99%
“…value of 16.3 for Factor VIII in the potent dispersing reagent guanidine hydrochloride appeared to rule out a noncovalently linked subunit structure (4). Recent studies of purified Factor VIII showed that it is a glycoprotein with a molecular weight of about one million (6) and that it is composed of disulfide-bound subunits which contain carbohydrate (5)(6)(7)(8). Sodium dodecyl sulfate gel electrophoresis, sedimentation equilibrium ultracentrifugation, and isoelectric focusing experiments performed in our laboratory (7) indicated that these covalently linked subunits are in fact identical with respect to size and electrical charge.…”
Section: Introductionmentioning
confidence: 99%